A formação da alteridade na experiência de leitura do gênero Bildungsroman presente em O fazedor de velhos, de Rodrigo Lacerda - Bueno, Ademir de Godoy (2018)
Rodrigo Lacerda’s novel ‘O Fazedor de Velhos’ (2009) (“Old People Maker”) adresses the narrator and protagonist’s search for his identity and ethical maturity. Lacerda’s approach to vital rites of passage such as the discovery of love and true vocation establishes a dialogue between the novel and an important literary genre: Bildungsroman. The focus on the protagonist’s formative journey through the sense of otherness, language mediation and the contrast between self-awareness and external reality revives the tradition of Bildungsroman. The Brazilian literature that the protagonist reads at school leads him to the answers he desperately looks for as well as awakens his passion for literature. The novel invites young readers to travel through the intertextuality of its utterances. In this literary universe, the story builds a link between classic and modern literatures, uttering the bases of the protagonist’s ethical and aesthetical formations through a joint reading with the reader. In this dissertation we describe and interpret the genre Bildungsroman which has formative purposes, based on Mass (2000), Mazzari (1999) and Pinto (1990). The protagonist’s trajectory in the first person singular aims to identify and suggest a humanistic, sociocultural and personal growth established with his peers through the sense of otherness triggered by literature at school and the discovery of himself in the world. Our analysis of the narrator’s hypothetical journey is based on Bakhtin (1992), Barthes (1973), Candido (1972) Colomer (2003), Todorov (2009), Calvino (2007), and Machado (2009)